2017
DOI: 10.1111/fare.12229
|View full text |Cite
|
Sign up to set email alerts
|

The Greek System: How Gender Inequality and Class Privilege Perpetuate Rape Culture

Abstract: Sexual assault on college campuses is a pervasive public health issue. It is important to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(45 citation statements)
references
References 54 publications
0
43
0
2
Order By: Relevance
“…Mason et al [12] found that people within academia consider research universities hostile for faculty to necessities of family life. Higher education institutions frequently lack accountability for gender-related inequities [46,47], and the recent controversy about policing microaggressions [48] distracts from the systematic creation of spaces where safety is not evenly distributed. A 2016 survey of American Anthropological Association members affirms this, indicating that “women are significantly more likely than men to have experienced a hostile workplace and most types of unwanted sexual behaviors” and to report that their institution did not handle claims of sexual harassment in accordance with federal law [4].…”
Section: Discussionmentioning
confidence: 99%
“…Mason et al [12] found that people within academia consider research universities hostile for faculty to necessities of family life. Higher education institutions frequently lack accountability for gender-related inequities [46,47], and the recent controversy about policing microaggressions [48] distracts from the systematic creation of spaces where safety is not evenly distributed. A 2016 survey of American Anthropological Association members affirms this, indicating that “women are significantly more likely than men to have experienced a hostile workplace and most types of unwanted sexual behaviors” and to report that their institution did not handle claims of sexual harassment in accordance with federal law [4].…”
Section: Discussionmentioning
confidence: 99%
“…The endorsement of “hegemonic gender roles rooted in the social dominance of men over women” (p.33) is prevalent on U.S. college campuses . Such norms reinforce traditional sexual scripts that depict men as sexual initiators and women as sexual gatekeepers .…”
mentioning
confidence: 99%
“…Gender adalah identitas yang melekat pada pria dan wanita karena konstruksi sosial-budaya masyarakat (Jozkowski & Wiersma-Mosley, 2017). Masalah gender muncul karena ketidakadilan peran antara laki-laki dan perempuan.…”
Section: Pendahuluanunclassified